Uterine leiomyomas and metastases: description of a case - T. I. Zakharova; Yu. G. Payanidi; K. I. Zhordania; N. I. Lazareva; E. V. Korzhevskaya (Опухоли женской репродуктивной системы)
Leiomyomas predominate among benign nonepithelial tumors of the corpus uteri. According to the data available in the literature, they occur in 25% of women above 35 years of age and constitute 33% of all gynecological diseases. Leimyoma is commonly an asymptomatic tumor and detectable in most cases at routine gynecological examinations. However, some forms of leiomyomas have a definite metastatic potential and, despite its benign morphological signs, may metastasize to the lung. Fatal cases resulting from tumor spread along the postcava to the right atrium are described.